Exploring English Teachers’ Self-Efficacy Beliefs in Teaching Reading Using Technology During The Post-Pandemic Era - Ardhiani, Nada; Ariani, Musli; Fitriyah, Siti Masrifatul (EFL Education Journal, 2024)
Self-efficacy beliefs is an important matter especially for teachers to have it as it enables an individual’s will to not give up easily if faced with challenging situations. By having high self-efficacy beliefs, teachers are expected to be able to effectively handle the difficulties they face in their classrooms so that they are able to select teaching methods, technique as well as the materials that will help them in teaching. However, little has been done on exploring specifically about English teachers’ self-efficacy beliefs in teaching reading using technology during the post-pandemic era. This study is done by implementing narrative inquiry which expected to be able to give detailed information about teachers’ personal experience in utilizing technology and how they evaluate their self-efficacy dealing with it. Thematic analysis was used to analyze the data obtained. Findings showed that despite implementing technology to increase students’ motivation is a success, it doesn’t apply in increasing students’ achievements. Therefore, to improve students’ achievements the teachers decided to focus on sharpening the students’ basic skills using school textbooks. Moreover, teachers also apply variations in teaching reading by implementing group work.